AtPGAP1 functions as a GPI inositol-deacylase required for efficient transport of GPI-anchored proteins. Issue 4 (16th August 2021) - Bernat-Silvestre, César; Sánchez-Simarro, Judit; Ma, Yingxuan; Montero-Pau, Javier; Johnson, Kim; Aniento, Fernando; Marcote, María Jesús
Abstract: Glycosylphosphatidylinositol (GPI)-anchored proteins (GPI-APs) play an important role in a variety of plant biological processes including growth, stress response, morphogenesis, signaling, and cell wall biosynthesis. The GPI anchor contains a lipid-linked glycan backbone that is synthesized in the endoplasmic reticulum (ER) where it is subsequently transferred to the C-terminus of proteins containing a GPI signal peptide by a GPI transamidase. Once the GPI anchor is attached to the protein, the glycan and lipid moieties are remodeled. In mammals and yeast, this remodeling is required for GPI-APs to be included in Coat Protein II-coated vesicles for their ER export and subsequent transport to the cell surface. The first reaction of lipid remodeling is the removal of the acyl chain from the inositol group by Bst1p (yeast) and Post-GPI Attachment to Proteins Inositol Deacylase 1 (PGAP1, mammals). In this work, we have used a loss-of-function approach to study the role of PGAP1 / Bst1 like genes in plants. We have found that Arabidopsis ( Arabidopsis thaliana ) PGAP1 localizes to the ER and likely functions as the GPI inositol-deacylase that cleaves the acyl chain from the inositol ring of the GPI anchor. In addition, we show that PGAP1 function is required for efficient ER export and transport to the cell surface of GPI-APs. Abstract : The inositol deacylase AtPGAP1 mediates the first step of glycosylphosphatidylinositol (GPI) anchor-lipid remodeling and is required for efficient transport of GPI-anchored proteins